DIMENSI INTERNASIONAL KASUS PAPUA - Elisabeth, Adriana (Pusat Penelitian Politik, 2006)
Issue on Papua has a strong international dimension. It will remain critical for Indonesian political bargaining when political violence and human rights abuse continue in Papua. The existence of multinational companies contributes to the international dimension of the Papuan case. Although most foreign countries stick on their commitment to support the integrity of Indonesian territory, the future of Papua depends on how the political and economic problems would be resolved.